Characteristics of the large corporation-based, bureaucratic model among oecd countries: An FOI model analysis - Zoltán Bartha; Andrea S. Gubik (DANUBE: Law, Economics and Social Issues Review, 2014)
Deciding on the development path of the economy has been a delicate question in economic policy, not least because of the trade-off effects which immediately worsen certain economic indicators as steps are taken to improve others. The aim of the paper is to present a framework that helps decide on such policy dilemmas. This framework is based on an analysis conducted among OECD countries with the FOI model (focusing on future, outside and inside potentials). Several development models can be deduced by this method, out of which only the large corporation-based, bureaucratic model is discussed in detail. The large corporation-based, bureaucratic model implies a development strategy focused on the creation of domestic safe havens. Based on country studies, it is concluded that well-performing safe havens require the active participation of the state. We find that, in countries adhering to this model, business competitiveness is sustained through intensive public support, and an active role taken by the government in education, research and development, in detecting and exploiting special market niches, and in encouraging sectorial cooperation.
Keywords: 330; Development Factors; Development Paths; FOI Model; OECD Countries